2018
DOI: 10.21037/jtd.2018.09.93
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-374b inhibits the tumor growth and promotes apoptosis in non-small cell lung cancer tissue through the p38/ERK signaling pathway by targeting JAM-2

Abstract: Background: MicroRNAs (miRNAs) are reportedly involved in various cancers. The present study aimed to investigate the role of miRNA-374b in cell viability, proliferation, apoptosis, and tumor formation in nonsmall cell lung cancer (NSCLC) in humans. Methods: The expression level of miRNA-374b in blood and tumor tissues from NSCLC patients was analyzed by quantitative reverse transcription polymerase chain reaction (qRT-PCR). A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Increasing evidence has demonstrated that numerous miRNAs are dysregulated in NScLc and that this dysregulation is a hallmark of NScLc (30)(31)(32). Recently, miRNAs have been identified as a novel player in gene regulation in NSCLC, with aberrant miRNAs expression serving pivotal roles in formation and progression of NScLc (33)(34)(35). A detailed investigation of cancer-associated miRNAs in NScLc is therefore crucial for identifying effective therapeutic targets for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that numerous miRNAs are dysregulated in NScLc and that this dysregulation is a hallmark of NScLc (30)(31)(32). Recently, miRNAs have been identified as a novel player in gene regulation in NSCLC, with aberrant miRNAs expression serving pivotal roles in formation and progression of NScLc (33)(34)(35). A detailed investigation of cancer-associated miRNAs in NScLc is therefore crucial for identifying effective therapeutic targets for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Tumorigenesis is a multistep process involving genetic and epigenetic alterations [ 7 ]. Epigenetics is a fundamental regulatory mechanism of gene expression that involves DNA methylation, histone modification, noncoding RNA regulation, and chromatin remodeling [ 8 11 ]. Epigenetic abnormalities are reportedly involved in tumor initiation, progression, and recurrence [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have broad effects on a wide range of biological behaviors, including cell proliferation, cell cycle, apoptosis, differentiation, metabolism, epithelial-mesenchymal transition, and metastasis 11,12,13. In particular, numerous miRNAs were identified to be dysregulated in NSCLC, including miR-374b,14 miR-500,15 miR-628,15 and miR-647 16. miRNAs may exert tumor-suppressive or oncogenic roles in the formation and progression of NSCLC based on the biological function of their target genes 17.…”
Section: Introductionmentioning
confidence: 99%